2019
DOI: 10.1016/j.psychres.2019.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Mapping cortical surface features in treatment resistant schizophrenia with in vivo structural MRI

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 82 publications
2
26
1
2
Order By: Relevance
“…This is in line with the current findings of TR linked to the genetics of schizophrenia (Owen et al, 2016). Furthermore, the current association between TR and PRS-SZ might indicate underlying factors in TR, as recent studies have revealed genetic pleiotropy between schizophrenia and phenotypes such as brain structure volumes (Terwisscha van Scheltinga et al, 2013;Smeland et al, 2018;Chen et al, 2019), immune related conditions (Andreassen et al, 2015) body mass index (Bahrami et al 2020) and lipids (Andreassen et al, 2013), all of which potentially related to antipsychotic drug treatment response (Barry et al, 2019;Hutcheson et al, 2014;Noto et al, 2015;Pillinger et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…This is in line with the current findings of TR linked to the genetics of schizophrenia (Owen et al, 2016). Furthermore, the current association between TR and PRS-SZ might indicate underlying factors in TR, as recent studies have revealed genetic pleiotropy between schizophrenia and phenotypes such as brain structure volumes (Terwisscha van Scheltinga et al, 2013;Smeland et al, 2018;Chen et al, 2019), immune related conditions (Andreassen et al, 2015) body mass index (Bahrami et al 2020) and lipids (Andreassen et al, 2013), all of which potentially related to antipsychotic drug treatment response (Barry et al, 2019;Hutcheson et al, 2014;Noto et al, 2015;Pillinger et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…A recent study comparing 145 APD-naive first-episode psychosis (FEP) patients and 147 controls found that CT decrease as an effect of age was more pronounced in patients, 15 while another showed CT reductions were greater in treatment resistant patients with SZ than nonresistant SZ. 16 As a measure, gyrification index is of particular interest due to its potential as a marker of abnormal neurodevelopment. 17,18 Altered gyrification patterns have been reported across different illness stages [19][20][21][22] and among first-degree relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal myelination in SZ has been mainly reported in white matter (WM) based on the diffusion tensor imaging (DTI) technique (Gangadin, Nasib, Sommer, & Mandl, ; Hamoda et al, ). Structural imaging of the gray matter (GM) has identified morphological changes such as reduced volume, thickness and surface area in SZ (Barry et al, ; Gao et al, ; Storvestre et al, ). Some studies suggest that in SZ, changes of myelination in WM might explain the morphometric change in GM since neural fibers mostly start from or end in the GM (Sasamoto et al, ).…”
Section: Introductionmentioning
confidence: 99%